Communication Experiences and Challenges of Kindergarten and Elementary Teachers in Online Learning during the COVID-19 Pandemic - Sri Seti Indriani; Ditha Prasanti (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
The increasing  number of patients recovering  from the COVID-19  and the decreasing number of people exposed to the infection seemed to raise the community’s hopes for  returning to face-to-face learning. Some schools have slowly implemented face-to-face learning. Teachers sincerely hope to optimize face-to-face learning soon. However, there are still pros and cons over face-to-face learning for fear of schools turning into COVID-19 clusters. The teachers complained about  various online learning problems, so they   applied  for  permission to conduct  face-to-face learning. The purpose of this research is to understand  teachers’ experiences in  online learning during the COVID-19 pandemic, including  positive and negative experiences  as well as  obstacles in the online learning during the pandemic. This study uses descriptive qualitative research methods, with data collection technique conducted through documentation studies as well as interviews with five kindergarten and elementary school teachers. The selection of research subjects used purposive sampling. The results of this study  revealed that the  teachers had  extraordinary experiences, both  negative and positive. The negative experiences during online learning are related to confusion, culture shock, dissatisfaction, stress, fatigue, and overwhelm, while the positive experiences are related to the ease of attending meetings simultaneously, carrying out activities at home and gaining new knowledge, especially in communication technology. Barriers and challenges experienced by teachers in  online learning during the pandemic are  technical and non-technical in nature.